Clinical and Capillaroscopic Modifications of the Psoriatic Plaque during Therapy: Observations with Oral Acitretin. (22nd September 2013) - Stinco, Giuseppe; Buligan, Cinzia; Errichetti, Enzo; Valent, Francesca; Patrone, Pasquale
Abstract : Psoriasis is considered to be an inflammatory autoimmune disease, where angiogenesis plays an undefined pathogenetic role. The well-known changes of the superficial microvasculature in the psoriatic plaque can be easily assessed in vivo by videocapillaroscopy. In the last years, several studies reported the clinical and capillaroscopic response of the psoriatic plaque during different topical and systemic treatments. In the present work we evaluated the effects of acitretin (0.8 mg/kg/day) on videocapillaroscopic alterations and the clinical response in 11 patients affected by plaque psoriasis at the baseline (T0) and after 4 (T1), 8 (T2), and 12 (T3) weeks. A clinical improvement during the treatment with a complete clinical healing of the plaque in 7 of the 11 patients was observed. The typical "basket-weave" capillaries of the psoriatic lesions showed a reduction of 65.4% in diameter at the end of the study; only 3 patients returned to a normal capillaroscopic pattern. As observed during previous our studies, we found a discrepancy between clinical and capillaroscopic results, with a far greater improvement in the first than in the second. This finding could be in agreement with a secondary role of blood vessels in the pathogenesis and persistence of psoriatic lesions.